Atomic absorption spectrophotometric determination of Lead and Cadmium metals accumulated in sediment and seawater samples collected from the shore of Tag-ibo, Iligan City, Philippines - Maglasang, Dale Jesther B. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2014)
The accumulation of Heavy metals, Pb and Cd were determined from the sediments and seawater samples collected from the shoreline of Tag-ibo, Iligan City. The concentrations of heavy metals were determined using Flame Atomic Spectroscopy (F-AAS). The average concentration of lead detected in the sediment samples was at the range of 5.2475 - 24.0824 ppm and that of cadmium was 3.5043-5.0471 ppm. The average concentration of lead in seawater samples ranged from 1.7474 - 7.8403 ppm and 0.0004 - 0.0233 ppm cadmium. Based on these results, there was a higher accumulation of Pb than Cd in both sediment and seawater samples. The level of lead in sediment and seawater samples exceeded the acceptable level while that in seawater samples were considered acceptable. The results indicated that Pb and Cd metals accumulated in the marine environment of Tag-ibo, Iligan City were relatively high. A parallel study on seagrass samples obtained from the same site indicated high concentration of Cd. Results of this current study are compared to that of the previous study conducted in 2001. It was observed that there has been a significantly large increase in the concentration of these metals.